The Implementation Of Mastery Learning In Bahasa IndonesiaA Site Study At Vocational High School Wisudha Karya Kudus - Hudlori, Hudlori (2012)
There are three objectives of the research as follows. First is to describe the characteristics of mastery learning planning in Bahasa Indonesia. Second is to describe the characteristics of mastery learning in Bahasa Indonesia. Third is to describe the characteristics of the assessment of learning outputs in Bahasa Indonesia. It is descriptive qualitative research and ethnography design which describes the implementation of mastery learning in Bahasa Indonesia. The data sources are events, documents, and informants. Techniques used in data collection are in-depth interview, documentation and observation. This research used data analysis techniques within the site. The activities in data analysis are data reduction, data display, and conclusion . The research results show three components. (1) Planning of mastery learning in Bahasa Indonesia include syllabus planning, establishment of MEC, and lesson plan. The syllabus is adopted from guidebooks of SBC, reformulated and expanded with character component. Setting MEC by taking the complexity of competence, intake of students and carrying capacity. Lesson plan prepared based on Process Standard. Module is composed for the students who follow non regular on the job training (OJT). (2) The implementation of mastery learning in Bahasa Indonesia refers to instructional design that includes preliminary, core, and closing. Preliminary contains apperception, pretest, learning objectives and descriptions of activities. Core activities include exploration, elaboration, and confirmation. Closing are conclusion, feedback, and posttest. The module is used for the students who follow non regular OJT. (3) The assessment includes accessing process and learning output use continuous assessment. Pretest is used to diagnose student learning difficulties. Posttest or formative test is to determine the completeness of competence. Students who have not reached MEC, will take remedial test or teaching and who have achieved mastery learning will be given enrichment. The assessment for the students who follow non regular OJT will use the task assessment in industry and formative test at school.